KETERAMPILAN PROSES SAINS PADA PRAKTIKUM IPA MATERI ASAM BASA PADA MAHASISWA PGMI IAIN PALU - Rahmawati (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palu, 2019)
The purpose of this study was to describe the science process skills of students of PGMI FTIK IAIN Palu on the science laboratory of Asam Basa. This research is a descriptive study conducted at the PGMI Study Program in September to October 2019. The research subjects were students of semester 3 of PGMI in the academic year 2019/2020 who took 28 natural science courses. Data in the form of students' Science Process Skills were obtained from the student performance appraisal in the science practicum on acid-base material. The results showed that students' science process skills varied in each category. For the category of skills using tools and materials, the average percentage for the 2 indicators is 83.05% or very high. For the category of observation skills, the average percentage for the two indicators is 83% or very high. For the grouping / classification skills category, the average percentage for the 2 indicators is 79% or in the high category. Whereas for communication skills where in this category there are 3 indicators with an average indicator of 82.5 or very high. Overall by averaging the percentage of all indicators obtained the percentage for science process skills in science lab, wet acid material is 82%. This shows that the science process skills of PGMI students are very high.